I'm that girl : living the power of my dreams - Chiles, Jordan; Laverne, Felice (Harper Influence, 2025)
This memoir from the two-time Olympian gymnast chronicles her journey to the awards podium while overcoming racism, childhood trauma and devastating setbacks, highlighting the importance of family support and the resilience of the human spirit​.